Functions of Juvenile Sociolects. Studies on Various Types of Verbal Exchange Between Young People and Adults - Augenstein, Susanne (De Gruyter, 1998)
The German Linguistic Studies Series is a comprehensive and outstanding forum in its field. It has borne the name of its subject in its title since the foundation of the series in the eighth decade of the last century. The series is comprehensive in the broad spectrum of topics covered (language levels, varieties, communication forms, epochs) in the range of research perspectives (theoretical and empirical studies, fundamental research and applications, interdisciplinarity with psychology, the social sciences etc.) and methodologies (the sole criterion is quality), in the rhythm of research (trends are perceived and also set, achievements are secured) and in the forms of presentation (monographs, textbooks, collected volumes, dictionaries). Professorial theses, outstanding doctoral theses, pioneering research findings from wider contexts, but also the surprising ‛stroke of genius' set the standards for inclusion in the series.
Description based on publisher supplied metadata and other sources
Keywords: Deutsch; Jugendsprache; Jugend; Dialog; Erwachsener